Touching from a distance: marketing the library and image building - Agha, Syed Salim (1994)
After making some general observations on the library and information scene it is pointed out that librarians seem to be out of touch with reality as is proven by their reactive, passive and traditionalistic approach to professional practice. The paper proposes that libraries need to inject relevancy, dynamism and proactivity in their activities. A marketing oriented management of libraries is proposed. After elaborating on a few basic concepts of marketing a working model of information marketing is set out. Each component of the model is elaborated upon. The message is brought home that in view of technological developments, changes in user needs and demands, competing services and other factors, librarians need a paradigm shift. Failure to do so could result either in the demise of the profession or a c; lowngrading of it. The adoption of the market approach. in information services has the potential of undertaking co-operative ventures in a borderless world. Image building is viewed as part of the marketing process. The image that society has of the profession is explored. The point is made that only when a profession has a positive impact on society that the status accorded to that profession" takes an upward shift. The impact of library activities on the public is discussed.Suggestions have been made to indicate factors which will help improve the image of " the library in the eyes of the public.